Topics in Cryptology - CT-RSA 2016 The Cryptographers' Track at the RSA Conference 2016, San Francisco, CA, USA, February 29 - March 4, 2016, Proceedings - Sako, Kazue (Security and Cryptology ;, 2016)
This book constitutes the refereed proceedings of the Cryptographer's Track at the RSA Conference 2016, CT-RSA 2016, held in San Francisco, CA, USA, in February/March 2016. The 26 papers presented in this volume were carefully reviewed and selected from 76 submissions. The focus of the track is on following subjects: secure key exchange schemes, authenticated encryption, searchable symmetric encryption, digital signatures with new functionality, secure multi party computation, how to verify procedures, side-channel attacks on elliptic curve cryptography, hardware attacks and security, structure-preserving signatures, lattice cryptography, cryptanalysis of symmetric key encryption, message authentication code and PRF-security, and security of public key encryption.